Electrochemical Characteristics of Fe₂O₃ Electrode in Alkaline Solution - Bui, Thi Hang (Old Journal, 2019)
To find the suitable materials for Fe/air battery anode, in this study Fe₂O₃ electrodes were prepared using commercial Fe₂O₃ materials of Aldrich. The size and morphology of Fe₂O₃ materials were observed by scanning electron microscope (SEM). The electrochemical properties of the Fe₂O₃ electrodes in alkaline solution were investigated using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The redox reaction rate of iron was slow, resistance of Fe₂O₃ electrodes increased during cycling. The effects of K₂S additive in electrolyte solution on the electrochemical properties of Fe₂O₃ electrodes were also investigated. The obtained results show that K₂S additive strongly affected on the electrochemical characteristics of Fe₂O₃ electrode such as improving redox reaction rate and cyclability, decreasing the electrochemical impedance of Fe₂O₃ electrode.